Sikap Orang Tua dengan Profesi Sebagai Petani dalam Mendorong Keberlanjutan Pendidikan Anak - Hizam, Ibnu; Pajrianti, Suptiana; Baharuddin, Baharuddin; Turmuzi, Ahmad (TAMADDUN: Jurnal Ilmu Sosial, Seni, dan Humaniora, 2023)
This study explores the attitudes of farmer parents in Lendang Nangka Village toward sustaining their children’s education during the 2022/2023 academic year. Using a descriptive qualitative approach with observation, interviews, and documentation, the research found varied parental perspectives. Many parents, despite economic hardships, strongly supported higher education for their children, driven by awareness of its importance, community influence, and religious values. Conversely, some regarded education merely as a formality. The study identified several supporting factors, including parental awareness, social encouragement, and spiritual motivation. Meanwhile, economic constraints, limited school facilities, and low student motivation were noted as major obstacles. Overall, the findings highlight that the majority of farming parents hold positive attitudes toward ensuring the continuation of their children’s education, reflecting resilience and commitment despite socioeconomic limitations.